Direct Electrosynthesis of Fe-TiC Composite from Natural Ilmenite in Molten Calcium Chloride. Issue 9 (1st January 2017) - Li, Shangshu; Zou, Xingli; Lu, Xionggang; Zheng, Kai; Li, Guangshi; Chen, Chaoyi; Xu, Qian; Zhou, Zhongfu
Abstract : Fe-TiC composite has been directly synthesized from natural ilmenite/carbon mixture precursors at 900–1000°C and 3.1–3.8 V in molten CaCl2 . The pressed natural ilmenite/carbon mixture pellet was used as the cathode, and an inert solid oxide oxygen-ion-conducting membrane (SOM) tube filled with carbon-saturated liquid tin as well as a graphite rod were employed as the anode, respectively. The reaction mechanism of the electroreduction process from ilmenite/carbon mixture to Fe-TiC has been discussed based on the Rietveld refinement analysis, and the characteristic of the produced Fe-TiC composite has also been systematically analyzed. The result shows that the SOM-based anode electrochemical process possesses higher current efficiency compared with the graphite-based anode electrochemical process. The electrochemical process shows a considerable reduction speed due to the reinforcement of the in-situ reduction-generated Fe. The produced Fe-TiC composite shows homogenous structure. In addition, nanoscale TiC particles can be further produced through a facile leaching process from the obtained Fe-TiC composite. The TiC powder synthesized through the electrochemical process is of great potential to be used for the refinement for aluminum and/or aluminum alloys.